Tetraploid induction of Mitracarpus hirtus L. by colchicine and its characterization including antibacterial activity - Kanoktip Pansuksan (2018)
Tetraploid plants were successfully induced for the first time in Mitracarpus hirtus L., by overnight immersion of shoot meristems in 0.1 % colchicine solution, followed by in vitro culture leading to plant regeneration. Examination of ploidy level by flow cytometric analysis and counting chromosome number at metaphase confirmed that original diploid plant (WT1) contained chromosome number as 2n = 2x = 28, whereas 2n = 4x = 56 was observed in the tetraploids induced with colchicine treatment (CC102 and CC110). Thicker root formation, larger stomata (1.3-2 times), and lower density of stomata (1.7-4 times) were observed in these tetraploid plants. After transplantation to the pot, tetraploid plant (CC110) showed higher fresh weights of aerial part and leaves (1.5 and 1.4 times respectively) than diploid. However, the methanolic extracts from leaves of tetraploid line CC102 showed inhibition against human pathogenic bacterium, S. aureus while WT1 and CC110 showed no activity. GC-MS revealed 40 unique compounds present in CC102, but absent in WT1 and CC110. Through hierarchical clustering analysis the 40 unique compounds in CC102 formed a cluster group found to correlate with anti-S. aurens activity. These results suggested that tetraploid M. hirtus CC102 created in this study provides a novel source of compounds useful in fighting infectious disease. © 2014 Springer Science+Business Media Dordrecht.